Environment-friendly two-component organic silicon adhesive for continuous gold stamping process as well as preparation method and application of environment-friendly two-component organic silicon adhesive

By using the platinum catalyst and organic bismuth catalyst system of the environmentally friendly two-component organic silicone adhesive, combined with the surface modification and gradient cross-linking of nano-silica fillers, the problems of VOCs pollution, high energy consumption and weak interfacial adhesion in the continuous hot stamping process are solved, and efficient and environmentally friendly hot stamping production is achieved.

CN120718595APending Publication Date: 2025-09-30ZHEJIANG SCI TECH UNIV SHAOXING KEQIAO RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510889924.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Existing solvent-based and water-based polyurethane adhesives have problems in the continuous hot stamping process such as VOCs pollution, high energy consumption, weak interface adhesion, and insufficient moisture and heat resistance, resulting in low production efficiency and high defective rate.

Method used

An environmentally friendly two-component organic silicone adhesive is used, including components A and B. Platinum catalysts are used to accelerate the hydrosilylation reaction and organic bismuth catalysts are used to promote hydroxyl condensation. Combined with surface modification and gradient cross-linking of nano-silica fillers, rapid curing and enhanced bonding are achieved.

Benefits of technology

It achieves low VOCs emissions, low energy consumption, fast curing and high wear resistance, improves the water washing fastness and interface bonding strength of the hot stamping layer, and reduces production costs and defective rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120718595A_ABST
    Figure CN120718595A_ABST
Patent Text Reader

Abstract

The invention discloses an environment-friendly two-component organic silicon adhesive for a continuous gold stamping process as well as a preparation method and application thereof, and belongs to the field of textile functional finishing aids. A hydrosilylation reaction is accelerated through a platinum catalyst, hydroxyl condensation is promoted through an organic bismuth catalyst, and the curing time is shortened by 50% or above; the surface modified nano silicon dioxide is uniformly dispersed in the adhesive layer to form physical crosslinking points, so that the cohesion strength is improved; no organic solvent is added into the environment-friendly double-group organic silicon adhesive, the content of VOCs is smaller than 10 g / L, and the environment-friendly double-group organic silicon adhesive meets the infant standard of Eco-Label and GB 18401-2020 National Textile Basic Safety Technical Specification of European Union; bubbles can be eliminated in the component A through a vacuum dispersion process, the transparency of an adhesive layer is ensured, and gradient crosslinking is achieved in the component B by controlling the hydrogen content gradient of hydrogen-containing siloxane (the component A is low in hydrogen content and the component B is high in hydrogen content).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textile functional finishing auxiliaries, and in particular to an environmentally friendly two-component organic silicone adhesive suitable for a continuous hot stamping process, a preparation method thereof, and application of the adhesive on fabrics. Background Art

[0002] In the textile hot stamping finishing industry, the performance of the adhesive directly determines the quality and production efficiency of the hot stamped fabric. Traditional processes generally use solvent-based polyurethane adhesives, which use organic solvents such as butanone and xylene as the medium. Although they can achieve rapid bonding between hot stamping film and fabric, they have significant environmental and technical drawbacks:

[0003] 1. Serious VOC pollution: Organic solvent volatilization accounts for 25%-30% of the total VOC emissions in the textile industry, which not only causes the air quality in the workshop to exceed the standard, but also requires expensive exhaust gas treatment equipment; 2. High energy consumption costs: To accelerate solvent volatilization, the baking process needs to maintain a certain high temperature. The annual energy consumption of a single production line exceeds 5 million kWh, and the carbon emission intensity reaches 0.8kgCO2 / m3 fabric; 3. Functional performance bottleneck: The water fastness of solvent-based adhesive film is only level 2-3 (GB / T 8629-2017 Household washing and drying procedures for textile testing), and the shedding rate of the hot stamping layer exceeds 50% after 15 washes.

[0004] In order to solve the pollution problem, water-based polyurethane adhesives have now appeared. However, the use of water-based polyurethane adhesives has great limitations. Although the water-based system uses water as the medium and the VOCs content can be reduced to below 50g / L, new problems are exposed in continuous hot stamping production:

[0005] 1. Low curing efficiency: The high heat of vaporization of water (2260kJ / kg) requires the film to be dried for an extended baking time of 90-120 seconds, forcing the production line speed to drop below 10m / min (the solvent-based process can reach 25m / min), reducing production capacity by more than 50%;

[0006] 2. Weak interfacial adhesion: The polarity difference between water-based polyurethane and hot stamping film (such as aluminum foil, PET aluminized film) is large, and the film is prone to interfacial separation due to thermal expansion and contraction. In the Martindale abrasion test, it can only withstand 200 rotations of friction (GB / T 21196 standard);

[0007] 3. Insufficient moisture and heat resistance: When baked at high temperatures, the film absorbs water and swells, resulting in "jagged" defects on the edges of the hot stamping pattern, and the defective rate is as high as 15%-20%. Summary of the Invention

[0008] The present invention mainly solves the technical problems existing in the above-mentioned prior art and provides an environmentally friendly two-component organic silicone adhesive for continuous hot stamping process, as well as a preparation method and application.

[0009] The above technical problems of the present invention are mainly solved by the following technical solutions: an environmentally friendly two-component organic silicone adhesive, comprising component A and component B;

[0010] The component A comprises the following components in percentage by weight based on 100% of the total weight:

[0011]

[0012]

[0013] The B component comprises the following components in percentage by weight based on 100% of the total weight:

[0014]

[0015] Preferably, the vinylsiloxane prepolymer is vinyl-terminated polydimethylsiloxane (Vi-PDMS) with a molecular weight of 5000-20000 Da;

[0016] The hydrogen-containing siloxane crosslinking agent is methyl hydrogen-containing siloxane, which is one of MQ silicone resin or linear PHMS.

[0017] Preferably, the platinum catalyst is a chloroplatinic acid-tetrahydrofuran complex or a platinum vinylsiloxane complex;

[0018] The organic bismuth catalyst is bismuth neodecanoate or bismuth naphthenate.

[0019] Preferably, the hydrogen content of the hydrogen siloxane crosslinking agent in component A is 0.1%-0.8%; and the hydrogen content of the hydrogen siloxane crosslinking agent in component B is 1.0%-1.5%.

[0020] Preferably, the tackifier is selected from one of silane coupling agent KH-560 and silane coupling agent KH-570.

[0021] Preferably, the surfactant is selected from polyether-modified silicone oil.

[0022] A method for preparing an environmentally friendly two-component organic silicone adhesive is characterized in that the compounding mass ratio of component A to component B is 5-15:1, and the pot life at 25°C after mixing is ≥30 minutes.

[0023] Preferably, the preparation of the A component specifically includes:

[0024] Add vinyl siloxane prepolymer, hydrogenated siloxane crosslinker, and tackifier into a planetary mixer and disperse at 1000 rpm for 30-60 minutes;

[0025] Add nano-silica filler, stir at high speed for 20-40 minutes, and finally degas under vacuum at -0.09 MPa for 10 minutes to obtain a white paste;

[0026] The preparation of the component B specifically includes: adding a platinum catalyst, an organic bismuth catalyst, a surfactant, and a nano-silica filler to a hydrogen-containing siloxane crosslinker, and stirring for 15-30 minutes in a dark environment to obtain a curing agent component;

[0027] Compounding process: Mix components A and B in proportion and mix at low speed for 5-10 minutes until uniform.

[0028] Preferably, the nano-silica filler is surface-modified with a silane coupling agent KH-570, and the modification conditions are: filler: coupling agent = 10:1, and the reaction is stirred at 80° C. for 2 h.

[0029] An application of an environmentally friendly two-component organic silicone adhesive, characterized in that it is used for bonding organic silicone adhesive to textile post-finishing hot stamping process, and the bonding process is:

[0030] The thickness of the coating layer is 50-100μm; it is cured at 80-120℃ for 10-30min or at room temperature with humidity ≥50% for 24h; the washing fastness of the hot stamping textile after finishing is ≥4.

[0031] The present invention has the beneficial effects:

[0032] 1. Dual catalytic system: platinum catalyst accelerates the hydrosilylation reaction (primary crosslinking), and organic bismuth catalyst promotes hydroxyl condensation (secondary crosslinking), shortening the curing time by more than 50%;

[0033] 2. Nano-filler reinforcement: Surface-modified nano-silica is evenly dispersed in the adhesive layer to form physical cross-linking points and enhance cohesive strength;

[0034] 3. Environmentally friendly: No organic solvents added, VOCs content <10g / L, meets the EU Eco-Label and GB18401-2020 "National Textile Basic Safety Technical Specifications" infant and toddler standards.

[0035] Key points of component A process: Nanofillers need to be surface modified with silane coupling agents to avoid agglomeration; vacuum dispersion process can eliminate bubbles and ensure the transparency of the adhesive layer.

[0036] Key points of component B process: The platinum catalyst needs to be prepared into a dilute solution in advance to avoid gelation caused by excessive local concentration; the hydrogen content gradient of the hydrogen-containing siloxane (low hydrogen in component A and high hydrogen in component B) is controlled to achieve gradient crosslinking. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1This is a schematic diagram of the mixing of component A and component B of the present invention;

[0038] Figure 2 This is a schematic diagram of a hot stamping application product of the present invention;

[0039] Figure 3 It is another schematic diagram of the hot stamping application product of the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be further specifically described below through embodiments and in conjunction with the accompanying drawings.

[0041] Example: An environmentally friendly two-component organic silicone adhesive for continuous hot stamping process and its preparation method and application, comprising component A (prepolymer component) and component B (curing agent component)

[0042] In a specific embodiment of the present invention, component A is a prepolymer component, and component B is a curing agent component. A method for preparing an environmentally friendly, two-component organic silicone adhesive suitable for a continuous hot stamping process is to physically mix components A and B, comprising the following steps:

[0043] (1) Preparation of component A

[0044] Add vinyl siloxane prepolymer, hydrogenated siloxane crosslinker, and tackifier into a planetary mixer and disperse at 1000 rpm for 50 min;

[0045] Nano-silica filler was added, stirred at high speed for 30 min, and finally vacuum degassed at -0.09 MPa for 10 min to obtain a white paste;

[0046] (2) Preparation of component B: Add a platinum catalyst, an organic bismuth catalyst, a surfactant, and a nano-silica filler to a hydrogen-containing siloxane crosslinker and stir for 20 minutes in a dark environment to prepare a curing agent component;

[0047] (3) Environmentally friendly, two-component silicone adhesive suitable for the preparation of continuous hot stamping process:

[0048] Mix components A and B in proportion and mix them at low speed for 10 minutes until they are uniform to obtain a two-component silicone adhesive.

[0049] (4) Hot stamping application

[0050] The hot stamping process is as follows: the thickness of the adhesive layer (the coating substrate is a hot stamping film or fabric) is 80μm. When the coating substrate is a hot stamping film, the bonding substrate is fabric (ordinary hot stamping fabric); when the coating substrate is fabric, the bonding substrate is a hot stamping film or fabric (special hot stamping fabric or composite fabric). After lamination, the adhesive layer is kept warm and cured at 90°C for 30 minutes, or cured at room temperature for 24 hours (humidity ≥ 50%); thus, the hot stamping finished fabric is obtained.

[0051] Examples 1 to 5

[0052] Component A was prepared according to the formula in Table 1, and component B was prepared according to the formula in Table 2.

[0053] The formula of component A is composed of the following components, and the listed proportions are by mass fraction:

[0054] Vinyl silicone prepolymer: 50%-70%

[0055] Hydrogenated siloxane crosslinker: 5%-20% (hydrogen content 0.1%-0.8%)

[0056] Nano-silica filler: 10%-25%

[0057] Tackifier: 2%-5% (selected from silane coupling agents KH-560, KH-570)

[0058] Table 1 Component A formula (unit: Kg)

[0059]

[0060] The B component comprises the following components in percentage by weight based on 100% of the total weight:

[0061]

[0062] Table 2 Component B formula (unit: Kg)

[0063]

[0064] Application Examples 1 to 5 and Comparative Application Examples 1 to 2

[0065] According to the compounding ratio in Table 3, component A and component B prepared in Examples 1 to 5 were compounded to obtain an environmentally friendly, two-component organic silicone adhesive. The auxiliary agent dosage and process designed in Table 3 were used to obtain normal ironing fabrics and special ironing fabrics, and the relevant properties of the two fabrics were measured.

[0066] Table 3 Preparation formula of environmentally friendly, two-component water-based polyurethane adhesive

[0067]

[0068] Table 4 Test results

[0069]

[0070] Description of the characterization methods involved in the examples and comparative examples:

[0071] With reference to GB / T 21196.2 (2007) “Textiles — Determination of abrasion resistance of fabrics by the Martindale method — Part 2: Determination of specimen damage”, a YG401H Martindale abrader (Nantong Hongda Experimental Instrument Co., Ltd.) was used to rub the surface of the finished fabric until the surface pattern was damaged.

[0072] With reference to GB / T 8629-2017 “Textiles—Household washing and drying procedures for testing”, a YG089S fully automatic fabric shrinkage testing machine (Nantong Hongda Experimental Instrument Co., Ltd.) was used to set the program for washing and drying the fabrics.

[0073] Reference: GB / T12490-2014 "Textiles—Tests for colour fastness—Colour fastness to domestic and commercial washing", the SW-24E washing colour fastness tester (Nantong Hongda Experimental Instrument Co., Ltd.) was used to test the colour fastness grade of hot stamping fabrics before and after soaping.

[0074] With reference to ZF / T 60011-2016 “Test method for peeling strength of composite fabrics”, a YG026Q fabric strength tester (Ningbo Textile Instrument Factory) was used to test the peeling strength of composite fabrics before and after washing.

[0075] Finally, it should be noted that the above embodiments are merely representative examples of the present invention. Obviously, the present invention is not limited to the above embodiments and is susceptible to numerous variations. Any simple modifications, equivalent variations, and modifications to the above embodiments based on the technical essence of the present invention are deemed to fall within the scope of protection of the present invention.

Claims

1. An environmentally friendly two-component organic silicone adhesive, characterized in that: It includes component A and component B; The component A comprises the following components in percentage by weight based on 100% of the total weight: Vinyl silicone prepolymer: 50%-70% Hydrogenated siloxane crosslinker: 5%-20% Nano-silica filler: 10%-25% Tackifier: 2%-5% The B component comprises the following components in percentage by weight based on 100% of the total weight: Platinum catalyst: 0.1%-0.5% Hydrogenated siloxane crosslinker: 60%-80% Nano-silica filler: 20%-35% Organic bismuth catalyst: 0.5%-2% Surfactant: 1%-3%.

2. The two-component organic silicone adhesive according to claim 1, characterized in that: The vinylsiloxane prepolymer is vinyl-terminated polydimethylsiloxane (Vi-PDMS) with a molecular weight of 5000-20000Da; The hydrogen-containing siloxane crosslinking agent is methyl hydrogen-containing siloxane, which is one of MQ silicone resin or linear PHMS.

3. The two-component organic silicone adhesive according to claim 1, characterized in that: The platinum catalyst is a chloroplatinic acid-tetrahydrofuran complex or a platinum vinylsiloxane complex; The organic bismuth catalyst is bismuth neodecanoate or bismuth naphthenate.

4. The two-component organic silicone adhesive according to claim 1, characterized in that: The hydrogen content of the hydrogen siloxane crosslinking agent in the component A is 0.1%-0.8%; the hydrogen content of the hydrogen siloxane crosslinking agent in the component B is 1.0%-1.5%.

5. The two-component organic silicone adhesive according to claim 1, characterized in that: The tackifier is selected from one of silane coupling agent KH-560 and silane coupling agent KH-570.

6. The two-component organic silicone adhesive according to claim 1, characterized in that: The surfactant is selected from polyether modified silicone oil.

7. A method for preparing an environmentally friendly two-component organic silicone adhesive, characterized by: The compounding mass ratio of the component A to the component B is 5-15:1, and the pot life at 25° C. after mixing is ≥30 min.

8. The method for preparing a two-component organic silicone adhesive according to claim 4, wherein: The preparation of the A component specifically includes: Add vinyl siloxane prepolymer, hydrogenated siloxane crosslinker, and tackifier into a planetary mixer and disperse at 1000 rpm for 30-60 minutes; Add nano-silica filler, stir at high speed for 20-40 minutes, and finally degas under vacuum at -0.09 MPa for 10 minutes to obtain a white paste; The preparation of the component B specifically includes: adding a platinum catalyst, an organic bismuth catalyst, a surfactant, and a nano-silica filler to a hydrogen-containing siloxane crosslinker, and stirring for 15-30 minutes in a dark environment to obtain a curing agent component; Compounding process: Mix components A and B in proportion and mix at low speed for 5-10 minutes until uniform.

9. The preparation method according to claim 5, characterized in that: The nano-silica filler was surface-modified with a silane coupling agent KH-570, and the modification conditions were: filler: coupling agent = 10:1, and the reaction was stirred at 80° C. for 2 h.

10. An application of an environmentally friendly two-component organic silicone adhesive, characterized by: Used for bonding organic silicone adhesive with textile post-finishing hot stamping process. The bonding process is: The thickness of the coating layer is 50-100μm; heat preservation and curing at 80-120℃ for 10-30min or room temperature curing at humidity ≥50% for 24h.